Effect of Wood Species and Layer Structure on Physical and Mechanical Properties of Strand Board - wahyu Hidayat; Mohamad I Sya'bani; Handian Purwawangsa; Apri H Iswanto; Fauzi Febrianto (Jurnal Ilmu dan Teknologi Kayu Tropis, 2011)
The objectives of this research were to evaluate the effect of wood species and layer structure on physical and mechanical properties of strand board made from Paraserianthes falcataria, Maesopsis eminii and Acacia mangium woods collected from planted forest in Bogor district, Indonesia. The densities of P. falcataria, M. eminii and A. mangium woods were 0.36, 0.41 and 0.46 g cm-3, respectively. Three types of layer structures namely perpendicular, parallel, and random orientation were applied. Methylene diisocyanate (MDI) resin with 7% resin amount (w/w) was used. The physical and mechanical properties of strand board were evaluated based on CSA 0437.0 standard. The results indicated that strand board manufactured from wood with lower density (P. falcataria) had higher mechanical properties (modulus of rupture, modulus of elasticity and internal bond) and lower dimensional stability (water absorption and thickness swelling) compared to strand board manufactured from higher density (A. mangium), vice versa. Strand orientation strongly affected the physical and mechanical properties of board with perpendicular orientation showed superior performance as compared to parallel and random orientation. Physical and mechanical properties of oriented strand board (OSB) made from fast growing tree species met the requirement of CSA 0437.0 standard for grade O-1 OSB panels.Key words: layer structure, methylene diisocyanate resin, strand board, tropical wood species,